Leaching behaviour of hexabromocyclododecane from treated curtains. (February 2016) - Stubbings, William A.; Kajiwara, Natsuko; Takigami, Hidetaka; Harrad, Stuart
Abstract: A series of laboratory experiments were conducted, whereby two HBCDD treated polyester curtain samples were contacted with deionised Milli-Q water as leaching fluid and HBCDD determined in the resulting leachate. As well as single batch (no replenishment of leaching fluid), serial batch (draining of leachate and replenishment with fresh leaching fluid at various time intervals) experiments were conducted. In single batch experiments at 20 °C, ΣHBCDD concentrations increased only slightly with increasing contact time (6 h, 24 h, and 48 h). This is supported by serial batch tests at 20 °C in which leaching fluid was replaced after 6 h, 24 h, 48 h, 72 h, 96 h, and 168 h. Data from these experiments show that while concentrations of HBCDD in leachate after 24 h cumulative contact time exceed those at 6 h; concentrations in samples collected at subsequent contact times remained steady at ∼50% of those in the 24 h sample. Consistent with this, leaching is shown to be second order, whereby a period of initially intense dissolution of more labile HBCDD is followed by a slower stage corresponding to external diffusion of the soluble residue within the textile. In experiments conducted at 20 °C, α-HBCDD is preferentially leached compared to β- and γ-HBCDD. However, at higher temperatures, the relatively more hydrophobic diastereomers are proportionally more readily leached, i.e. raising the temperature from 20 °C to 80 °C increased concentrations of γ-HBCDD in the leachate by a factor of 28–33 while corresponding α-HBCDD concentrations only increased by a factor of 4.3–4.8. Highlights: We study HBCDD leaching from contacting a treated textile with deionised water. Leaching of HBCDD from textiles is shown to be a second order process. α-HBCDD is preferentially leached compared to β- and γ-HBCDD at 20 °C. At 80 °C γ-HBCDD is proportionally more readily leached than α-HBCDD. A max. total HBCDD conc. of 20, 000 ng L −1 was detected in the leachate.